The Corporate Purpose of Spanish Listed Companies: Neurocommunication Research Applied to Organizational Intangibles - Mañas-Viniegra, Luis; González-Villa, Igor-Alejandro; Llorente-Barroso, Carmen (Frontiers in Psychology, 2020)
Purpose driven companies have developed their corporate culture with a commitment to stakeholders, Sustainable Development Goals, and social responsibility, prioritizing the management of organizational intangibles over capital. The overall objective of this research is to gain knowledge regarding the attention and emotional intensity registered by young Spanish university students when visualizing corporate purpose versus corporate visual identity, as well as the image of the Chairman of the main Spanish companies quoted on the IBEX 35. The techniques of eye tracking and galvanic skin response have been used with 31 Spanish university students. The results suggest that brands with the highest brand equity in the Interbrand (2019) ranking are also the ones that receive the highest levels of attention and emotional arousal, and that a well-formulated corporate purpose is not enough to satisfy the public if company credibility is low due to previous perceptions of an organization.